The water's edge: the Jackson amendment as a case study of the role domestic politics plays in the creation of American foreign policy (Volume 1) - Stern, Paula, 1945- (Tufts University Tisch Library, 2026)
A thesis presented to the faculty of the Fletcher School of Law and Diplomacy in partial fulfillment of the requirements for the degree of doctor of philosophy; 1 online resource.; "April 1976."; Volume 1 of 2.